Microbiological Survey of the Human Gastric Ecosystem Using Culturing and Pyrosequencing Methods - Delgado, Susana; Cabrera-Rubio, Raúl; Mira, Alex; Suárez, Adolfo; Mayo, Baltasar (Microbial ecology, 2013)
Stomach mucosa biopsies and gastric juices samples of 12 healthy persons were analysed by culturing in selective- and non-selective-rich media. Microbial DNA from four mucosal samples was also amplified by nested PCR using universal bacterial primers, and the 16S rDNA amplicons pyrosequenced. The total number of cultivable microorganisms recovered from the samples ranged from 10 2 to 10 4 cfu/g or ml. The isolates were identified at the species level by PCR amplification and sequencing of the 16S rDNA. Isolates belonged mainly to four genera; Propionibacterium, Lactobacillus, Streptococcus and Staphylococcus. A total of 15,622 high-quality 16S rDNA sequence reads were obtained by pyrosequencing from the four mucosal samples. Sequence analysis grouped the reads into 59 families and 69 genera, revealing wide bacterial diversity. Considerable differences in the composition of the gastric microbiota were observed among the subjects, although in all samples the most abundant operational taxonomic units belonged to Streptococcus, Propionibacterium and Lactobacillus. Comparison of the stomach microbiota with that present in other parts of the human gastrointestinal tract revealed distinctive microbial communities. This is the first study in which a combination of culture and culture-independent techniques has been used to explore the bacterial diversity of the human stomach.